REPAIRING AT THE APP CLINIC: A CASE STUDY OF AN ONLINE WELLNESS APPLICATION - Slaker, Janine Sakiko (AoIR Selected Papers of Internet Research, 2015)
Presented is a brief account of a six-month ethnographic case study of an Internet-communications technology startup. This company has designed an online application for the purpose of increasing wellness of individuals in the workplace. By way of curated prompts of self- and group-reflection and self-tracking, the company seeks to transport workers through an architected experience that leads to greater production through holistic awareness. The methods used for this study include in-depth, unstructured interviews, participant-observation of the employees, and platform study. The company, which has a core group of four employees, includes a CEO, a product manager, a developer, and a designer. Following, is a summary of my observations in which I attempt to describe how the employees of this startup imagine the body in need of care. I then conclude with a description of how I see the discussion expanding to include their online platform and how it can be framed as a clinic for care.